Chế tạo nanocompozit trên cơ sở cao su nhiệt dẻo polyvinylclorua/cao su butadien-acrylnitril và nanoclay bằng phương pháp lưu hóa động - Minh, Đào Thế; Hưng, Hoàng Tuấn; Kháng, Đỗ Quang; Hội, Nguyễn Văn (Vietnam Journal of Chemistry, 2014)
The effect of blend composition and dynamic vulcanisation by dicumyl peroxide (DCP) on processability, mechanical properties of Polyvinylchloride/Acrylonitrile Butadiene Rubber Blends (PVC/NBR) were investigated. Blends were prepared in Haake Mixer at 180oC and a rotor speed of 50 rpm. It was found that 80 PVC/20 NBR blends have high mechanical property and are easy to process. Afterwards, the new thermoplastic elastomer/organoclay nanocomposites were prepared by the melt intercalation method. The 80 PVC/20 NBR/2% organoclay nanocomposite was intercalated, as evidence by X-ray differaction and TEM image. The scanning electron microscopy (SEM) showed that the compatibility and the dispersion of NBR  in PVC matrix were improved thanks to nanoclay